Multidimensional analogues of the Riemann–Hilbert boundary value problem - Paliokas, Eugenijus (Mathematical Modelling and Analysis, 2007)
Multidimensional generalizations of the Cauchy‐Riemann systems and two different types of analogues of the Riemann–Hilbert boundary value problems for these systems are considered.First Published Online: 14 Oct 2010